Efektivitas Strategi Pembelajaran Kooperatif dalam Meningkatkan Prestasi Akademik dan Keterampilan Sosial pada Mata Pelajaran Pendidikan Agama Islam - Isro Royhanna; Irma Suriani; Gusmaneli Gusmaneli (Jurnal Budi Pekerti Agama Islam, 2026)
Education in the 21st century demands a paradigm shift from passive learning to collaborative and student-centered learning, in line with the Merdeka Curriculum’s emphasis on the value of mutual cooperation. However, challenges arise due to the younger generation’s heavy reliance on technology, which tends to foster individualism. This study aims to examine the implementation of cooperative learning strategies as a solution to foster social interaction and student engagement. Cooperative learning strategies constitute a conceptual framework for a series of learning activities within heterogeneous small groups to achieve shared goals. Through a literature review, it was found that the implementation of these strategies involves systematic steps ranging from group formation, problem-solving discussions, to group recognition. The results of the analysis indicate that cooperative strategies have significant advantages in enhancing students’ self-confidence, independence, responsibility, and academic achievement. Although they have limitations regarding time management and the need for specific skills among educators, these strategies are considered highly relevant for fostering students’ character to be inclusive, tolerant, and capable of collaborating amidst differences.